Ruang Publik, Bahasa, Dan IdentitasStudi Kasus Pada Pusat Kota Madiun, Jawa Timur - Erlita Rusnaningtias; Magna Aurizza Wibowo (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2026)
This paper aims to explore the influence of foreign icons on the language(s) used in public signage or the Linguistic Landscape (LL). The location of the research was “Pahlawan Street Center” (PSC), one of the tourist destinations in Madiun, East Java Province, Indonesia. The approach used in this study is a qualitative descriptive, and the data collected from public signs, traffic signs, street and building names were analyzed using the LL theory by Landry and Bourhis (1997). From this study, 13 languages were identified across 211 LL items, including Indonesian, English, Javanese, regional languages, and other foreign languages. Indonesian remains the dominant language used in LLs created by both government and individuals, while English holds the second-highest position, especially in LLs. Regarding the function of language in LLs, Indonesian is more commonly used in LLs created by the government, such as signs or regulations, serving an informational function; whereas foreign languages are often found in LLs created by individuals, such as commercial LLs, serving a symbolic function. Finally, the development of PSC as an area showcasing global landmarks reflects Madiun City’s efforts to adapt to global developments and enhance its appeal in the eyes of the world. However, this influence of globalization poses challenges related to preserving local culture, especially in terms of language and cultural identity.